2022
DOI: 10.1177/19322968221139873
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Continuous Glucose Monitoring in Adolescents and Young Adults With Type 2 Diabetes Can Improve Quality of Life

Abstract: Objective: Real-time continuous glucose monitoring (CGM) is effective for diabetes management in cases of type 1 diabetes and adults with type 2 diabetes (T2D) but has not been assessed in adolescents and young adults (AYAs) with T2D. The objective of this pilot interventional study was to assess the feasibility and acceptability of real-time CGM use in AYAs with T2D. Methods: Adolescents and young adults (13-21 years old) with T2D for six months or more and hemoglobin A1c (A1c) greater than 7%, on any Food an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…We demonstrate in this pilot that CGM wear in youth with T2D is feasible and effective. Similar to a recent report, 3 participants in our pilot study also expressed high satisfaction with the CGM device. In our cohort, however, we identified an improvement in HbA1c after 3 months of CGM wear, despite comparable mean HbA1c.…”
supporting
confidence: 91%
“…We demonstrate in this pilot that CGM wear in youth with T2D is feasible and effective. Similar to a recent report, 3 participants in our pilot study also expressed high satisfaction with the CGM device. In our cohort, however, we identified an improvement in HbA1c after 3 months of CGM wear, despite comparable mean HbA1c.…”
supporting
confidence: 91%
“…To our knowledge, only 1 other study has elicited perspectives about CGM use among AYAs with T2DM; this study assessed changes in quality of life and acceptability in AYAs who completed a 12-week period of real-time CGM use. 11 AYAs reported improved quality of life (n = 7 evaluated) and general convenience and acceptability of CGM use (1 focus group of 5 AYAs). However, studies of adolescents with type 1 diabetes have shown that perceptions of CGM use may be divided.…”
Section: Discussionmentioning
confidence: 99%
“…9 For youth with T2DM, CGM could serve to minimize the burden of frequent blood glucose monitoring, which may ultimately facilitate modifications to medication or health behaviors via improved glycemic awareness. Evidence related to clinical benefits for youth with T2DM has been limited 10 but is now emerging, 11 following trends in adult T2DM care. 12 A first step toward planning for widespread uptake of CGM among youth with T2DM is understanding patient perspectives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…First and foremost, all children with T2D should receive comprehensive education on self-management that includes teaching glycemic self-monitoring as long as needed and during periods of acute illness when symptoms of hyper- or hypoglycemia most often occur. Glucose monitoring or possibly even interstitial glucose sensor monitoring becomes imperative in patients on insulin therapy [ 85 ]. Just as for patients with T1D, HbA1c should be periodically monitored [ 79 ].…”
Section: Treatmentmentioning
confidence: 99%